2020
DOI: 10.1016/s2214-109x(20)30366-1
|View full text |Cite
|
Sign up to set email alerts
|

Immediate impact of stay-at-home orders to control COVID-19 transmission on socioeconomic conditions, food insecurity, mental health, and intimate partner violence in Bangladeshi women and their families: an interrupted time series

Abstract: Summary Background Stay-at-home orders (lockdowns) have been deployed globally to control COVID-19 transmission, and might impair economic conditions and mental health, and exacerbate risk of food insecurity and intimate partner violence. The effect of lockdowns in low-income and middle-income countries must be understood to ensure safe deployment of these interventions in less affluent settings. We aimed to determine the immediate impact of COVID-19 lockdown orders on women and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
458
4
15

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 401 publications
(506 citation statements)
references
References 27 publications
(32 reference statements)
29
458
4
15
Order By: Relevance
“…During this quarantine, many studies have used the online form to reach their potential participants [30] on home confinement. To a lesser extent, telephone surveys have been used, particularly in longitudinal studies, with a pre-established participant base [31].…”
Section: Introductionmentioning
confidence: 99%
“…During this quarantine, many studies have used the online form to reach their potential participants [30] on home confinement. To a lesser extent, telephone surveys have been used, particularly in longitudinal studies, with a pre-established participant base [31].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the pandemic appears to be a largely negative experience for many people around the world (Benke et al, 2020;Ebrahimi et al, 2020;Fiorenzato et al, 2020;Gao et al, 2020;Hamadani et al, 2020;Holman et al, 2020;Huang & Zhao, 2020;Kalaitzaki, 2020;Lee, 2020;Marashi et al, 2020;Mazza et al, 2020;Ozamiz-Etxebarria et al, 2020;Qiu et al, 2020;Roy et al, 2020;Wang et al, 2020; Zacher & Rudolph, 2020), and we have reported a substantial proportion in our sample of Australians being negatively affected during lockdown. Numerous studies have indicated that shared experiences of pain, adversity, and/or hardship have the potential to act as social bonding experiences (some examples: Bastian, Jetten, & Ferris, 2014;Bastian, Jetten, Hornsey, et al, 2014;Bastian et al, 2018;Breslin, 2019;Shaw et al, 2020).…”
Section: Perceived Change In Social Relationships and Communication Pmentioning
confidence: 60%
“…Quarantine (lockdown) actions during prior pandemics such as SARS and MERS have been found to negatively affect psychological well-being (Brooks et al, 2020). Emerging research on people's experience during COVID-19 lockdowns around the world are producing similar findings of increased levels of stress, anxiety and depression (Benke et al, 2020;Ebrahimi et al, 2020;Fiorenzato et al, 2020;Gao et al, 2020;Hamadani et al, 2020;Holman et al, 2020;Huang & Zhao, 2020;Kalaitzaki, 2020;Lee, 2020;Marashi et al, 2020;Mazza et al, 2020;Ozamiz-Etxebarria et al, 2020;Qiu et al, 2020;Roy et al, 2020;Wang et al, 2020;Zacher & Rudolph, 2020). Some of these researchers have considered how preoccupation with COVID-19 and increased social media exposure contribute to COVID-19 stress (Gao et al, 2020;Holman et al, 2020;Hsiang et al, 2020;Lee, 2020;Roy et al, 2020).…”
Section: The Impact Of Covid-19 Lockdown On Mental Health Around Thementioning
confidence: 99%
“…In addition, the research revealed a significant drop in the percentage of households who could not afford a 3 meals per day diet- about 24% households of urban slum areas and 14% rural households could not afford a 3 meals per day diet. In order to explore the impact of general holidays of the Government of Bangladesh to contain the spread of COVID-19 virus on household’s socio-economic conditions, food insecurity, mental health and intimate partner violence, Hamadani et al ( 2020 ) surveyed mothers from 2417 households of Rupganj Upazila of Narayanganj District of Bangladesh where they found that during the general holiday, the number of households experiencing food insecurity increased by 51.7%. They found that the proportion of moderately food insecure households increased from 5.6% (pre-lockdown condition) to 36.5% and for the severely food insecure households, the change was from 2.6 to 15.3%.…”
Section: Empirics Of Food Poverty Vulnerability and Inequalitymentioning
confidence: 99%